(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This survey research was conducted to determine the level of soft skills and the job performance of the teaching staff at A Higher Education Institution in Novaliches, Quezon City. Also, to determine if there is a significant relationship between the levels of soft skills the teachers possess and their job performance at work in the school. In this research, soft skills in job performance sought to determine whether they meet the needs of students and fulfill their jobs as teachers. Some examples of soft skills are communication, teamwork, critical thinking, problem-solving, etc. These instances help to enhance the skills of a teacher, which, as a result, can be relevant to their work. A descriptive-quantitative research design was used by the researchers in this study. The researchers selected a sample based on their knowledge of the study and population. The participants are chosen based on the purpose of the sample. Forty (40) teaching staff were selected to participate in the study. The researcher-made questionnaire was developed as a guide to collect data. It was validated by the research adviser, professional experts, and statistician before administering it to the respondents. It was administered to the respondents through Google Forms and face-to-face. The results showed that most of the respondents of this study are females aged 26 - 30 years old, with the highest educational attainment of a bachelor’s degree and 4 - 6 years of service in teaching. The findings of this study revealed that the level of soft skills of the teaching staff is “excellent” (OWM = 4.60) in terms of communication, teamwork, critical thinking, and flexibility, and the level of job performance of teaching staff is “excellent” (OWM = 4.54) in terms of planning and preparation, classroom environment, instruction, student progress, and professional work habits. Also, based on the findings, a major concern encountered by the teaching staff with their soft skills is having too much multitasking, reflecting their job performance. The findings were utilized to construct a guideline, as this study proposed, on how to improve the teacher’s soft skills and job performance to accomplish their job effectively and skillfully towards their students, coworkers, and superiors.